Bibliometric study on family refusal of tissue and organ donation for transplants from 1990 to 2004 - Moraes, Edvaldo Leal de; Massarollo, Maria Cristina Komatsu Braga (Brazilian Journal of Transplantation, 2006)
The lack of organs for transplantation have been concerning societies all over the world because the family refusal is a limiting factor to face the increasing demand on the high number of transplantation. Purposes: This study had as target to identify the national and international amount of scientific production on the family refusal, even considering the identified scientific production of quantity, year of publishing, country of origin, and categorizing the scientific production on the identified themes. Methods: To get the bibliometric study performed; the Medline and Lilacs databases having the organ donation X family refusal as describers were used. Results: Fifty-two (52) MEDLINE articles, and one (1) LILACS article also indexed in Medline were found. The study has shown that USA is the main publisher country of the intellectual production on this subject (48.1%) and the country which mostly produced works on family refusal of organ donation (21.1%). Conclusion: The results attained show that the international scientific production on family refusal has increased, and the United States is the country with the majority of works published. On the other hand, Latin America countries, such as Brazil, have produced few works on the subject (1.9%), evidencing the need to increase the scientific production in this field.